ChemInform Abstract: A Useful Methoxyvinyl Cation Equivalent: α‐t‐Butyldimethylsilyl‐α‐methoxyacetaldehyde. Issue 39 (September 2015) - McCune, Christopher D.; Beio, Matthew L.; Friest, Jacob A.; Ginotra, Sandeep; Berkowitz, David B.
Abstract Addition of Grignard reagent or lithiated acetylide nucleophiles to the title aldehyde affords β‐hydroxysilanes.